Transforming Social Capital into Performance via Entrepreneurial Orientation. Issue 4 (November 2020) - Nguyen, Long Thanh; An, Jake; Ngo, Liem Viet; Hau, Le Nguyen
Despite the importance of social capital (e.g. external network ties, social interaction, and relationship quality) and entrepreneurial orientation (e.g. proactiveness, innovativeness, and risk taking) for firm performance, little is known about the mechanisms that benefit firms from the interplay among these factors. It has also been unclear which entrepreneurial processes or activities assist in transforming social capital into positive performance outcomes. In this study, we clarify how and why entrepreneurial orientation assists in transforming social capital into firm performance. A survey of 198 entrepreneurs in Vietnam shows that entrepreneurial firms need both bridging and bonding capital (i.e. external network ties and social interaction) for enhanced relationship quality. While proactiveness mediates the impact of relationship quality on firm performance, findings show no support for the mediating role of innovativeness and risk taking. In other words, proactiveness converts relationship quality into enhanced firm performance, while innovativeness and risk taking do not.